1984
DOI: 10.1037/0022-0167.31.4.558
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive mediational paradigm for research on counseling.

Abstract: Arguments are presented for obtaining relatively direct data on counselor and client cognitive processes during counseling when conducting research on counseling outcomes. A theory of cognitive processing in counseling is presented, and a research paradigm is described that considers cognitive processes and attempts to link such processes to the interactive behaviors of counselors and clients and to client learning outcomes. Some of the methodological and conceptual issues related to the operationalization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 40 publications
1
76
0
Order By: Relevance
“…Research has suggested that a climate of openness and transparency in professional performance assessment during counselor preparation may be critical to students' accurate perceptions of the assessment process, their trust in relationships with faculty members, and most importantly, their future willingness to preserve the ethical integrity of the counseling profession through an active gatekeeping role. Martin (1984) used the term transparency to describe the accuracy of client perceptions of counselor intentions. Applied to counselor education, transparency refers to the accuracy of student counselors' perceptions of the intentions of a counselor education program.…”
Section: Student Perceptions Of the Professional Performance Assessmementioning
confidence: 99%
“…Research has suggested that a climate of openness and transparency in professional performance assessment during counselor preparation may be critical to students' accurate perceptions of the assessment process, their trust in relationships with faculty members, and most importantly, their future willingness to preserve the ethical integrity of the counseling profession through an active gatekeeping role. Martin (1984) used the term transparency to describe the accuracy of client perceptions of counselor intentions. Applied to counselor education, transparency refers to the accuracy of student counselors' perceptions of the intentions of a counselor education program.…”
Section: Student Perceptions Of the Professional Performance Assessmementioning
confidence: 99%
“…Thus, most of the previous social influence research has treated the client as a rather passive agent. Recently in both counseling and clinical psychology, writers have conceptualized counseling as an exchange of information, with the client as an active processor of information (Heppner, 1989;Heppner & Krauskopf, 1987;Hollon & Kriss, 1984;Martin, 1984Martin, , 1987. We suspect that client characteristics will become more prominent variables in the change process as clients are conceptualized in this way and as client characteristics are examined in relation to the amount and type of information processed, cognitively and affectively.…”
Section: Client Variablesmentioning
confidence: 99%
“…We recommend that the client be conceptualized as an active processor of information within the influence process (Heppner, 1989;Heppner & Krauskopf, 1987;Martin, 1984Martin, , 1987McGuire, 1985;Petty & Cacioppo, 1986). It is unknown how clients process information they receive in counseling, and how this may either facilitate or hinder therapeutic changes.…”
Section: Summary and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…1985;Martin, 1984;Morran, Kurpius & Brack, 1989). They have, however, received little attention within the group work field.…”
Section: Contribution 4: D Keith Morranmentioning
confidence: 94%